Capitalism as an Ideology Criticized through Allegory in Ryūnosuke Akutagawa’s Kappa - Setiowati, Rosa Vania; Wardani, Elisa Dwi (Universitas Sanata Dharma, 2016)
Ryunosuke Akutagawa‟s novel entitled Kappa (1926) is believed to be the allegory of Japanesetructure of politics and the economy in the 20th century Japan. Yet, none of the study focused on describing the function of this allegorical Kappaland and its society to criticize the system of capitalism in Japan. Thus, the writer finds it important to scrutinize how the author of the story employs the allegory, as a rhetorical device of literary works, to criticize the reign of the dominant class in Japanese systems of politics and economy. Focusing on the allegorical characters, setting, and significant events, this study seek for, the evidence that Kappa is the representation of Japanese society. Some events are created to signify the real condition of Japan in the early of 20th century, after the Meiji Restoration. The effect of industrial revolution brings several questions, including the role of the State and its apparatuses, to be problematized in this study. In addition, Akutagawa points out some of the lacks and shortcomings of humans through the allegorical characters and events in Kappaland. The settings are employed to show the life-likeness of Kappa and humans and support the wholeness of allegory. Analysis on parallelism of Kappaland and Japan is deemed important to reveal the criticism Akutagawa raises through the characters and the significant events. The setting of the story is pretty similar to what Japan was experienced, for instance the massive industrial production linked to the capitalist mode of production, the accumulation of power and wealth to the small amount of the dominant class. It is observed that Kappa is a disgusting and deformed mirror Akutagawa gives to humans to reflect their life. Keywords: capitalism, ideology, Akutagawa